Traumatic hip dislocations in children and adolescents: diagnostic challenges and the significance of MRI imaging : a multi-center study - Braun, Mirjam Esther Evi; Fernandez Fernandez, Francisco; Riha, Lena; Schmal, Hagen; Schmittenbecher, Peter; Schneidmueller, Dorien; Strüwind, Christoph; Schwerk, Philipp; Reineke, Sebastian; Traub, Frank; Ihle, Christoph; Lieber, Justus; et al. (European journal of trauma and emergency surgery, 2025)
Traumatic hip dislocations in children and adolescents are rare but can lead to severe outcomes like avascular necrosis. Delayed reductions, often due to overlooked dislocations in initial imaging, pose a major risk. The variability in symptoms and emergency care challenges early diagnosis. This multi-center study evaluates diagnostic approaches to enhance protocols for identifying traumatic hip dislocations in childhood.